A new genus and rare genera of Macrocentrinae from the Oriental region (Hymenoptera: Braconidae) - Oanh, Nguyen Thi; Long, Khuat Dang; Achterberg, Cornelis Van; Nghiep, Hoang Thi; Hiep, Nguyen Duc (Zootaxa, 2024)
The description of Neurogoniella van Achterberg & Long, gen. nov. (Braconidae: Macrocentrinae) designated type species: Macrocentrus crassinervis Nixon, 1950), is based on the holotype from India and a recently collected series from Vietnam. For the redescription a female of M. crassinervis Nixon from Vietnam is used. Additionally, Leptozele radiellanus (He & Chen) comb. nov. and Rectizele parki van Achterberg are newly recorded for Vietnam’s fauna. Leptozele radiellanus is redescribed and illustrated, and a key to Oriental macrocentrine genera is provided.